PENGEMBANGAN PETUNJUK PRAKTIKUM BIOLOGI PADA MATERI JAMUR DENGAN POLA PEMBERDAYAAN BERPIKIR MELALUI PERTANYAAN (STUDI KASUS DI KELAS X.3 SMA MUHAMMADIYAH 1 METROTAHUN PELAJARAN (2013/2014) - Anggraini, Astri (Bioedukasi Jurnal Pendidikan Biologi, 2016)
The purpose of this research is to produce practical guidance with patterns of thinking empowerment by questioning. This researchdevelopment starting from the definition phase, the planning phase, and the development phase. The development phase includes three steps, namely validation by expert teacher and two lecturers, product revision, and produk testing. Validation expert is testing materials and the quality of the results obtained 100% with a very high category. Readability level got result>60% with ten indicators of getting high category. Aplicatibility level got result> 60% with two indicators of gettinh veri high category and eight indicators of getting high category. Practice guidancehas beendevelopedin accordancewith thecriteria ofgoodpracticeguidance. Practice guidance developed has advantages which can develop students critical thinking skills, but this guide also has the disadvantage that only limited one material is Mushroom material.KataKunci:Penelitiandanpengembangan,Â  petunjuk praktikum, berpikir melalui pertanyaan.